Pendidikan Ilmu Astronomi Dari Historis Sampai Heliosentris - Nabil, Nabil (STIT Al-Marhalah Al-Ulya Bekasi, 2018)
Science in human life is very important to illuminate every walk of life, both physical (material) and metaphysical (immaterial). The universe was born millions and even billions of years ago, so many astronomical physicists calculate the origin of the universe, so the creation of the theory of bigbang, black holes, dark energy, dark matter, newton gravity, etc. Astronomy is important in teaching to know the phenomena of the universe (general), and to know times of worship (specifically). Before entering the science, it is better to know the history of astronomy, both the history of theory, and the figures then the hierarchy between geocentric and heliocentric in several views, both from the view of a character, as well as the view of the scriptures. Indeed, when humans think about the universe, in this case about the center of the universe there will be a hierarchy with the scriptures. This is a matter between different reason and revelation. Therefore, in this paper I touch on the issue of Heliocentric and Geocentric. And do not forget the astronomical figures from the West and East.